2017
DOI: 10.1590/0001-3765201720170001
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of essential oils of Ocimum basilicum and Cymbopogum flexuosus in the sedation and anaesthesia of Nile tilapia juveniles

Abstract: This study aimed to verify the sedative and anaesthetic effect of the essential oils of basil (Ocimum basilicum) (EOOB) and lemongrass (Cymbopogum flexuosus) (EOCF) in Nile tilapia juveniles. The fish were transferred to aquaria containing different concentrations of each essential oil: 10, 25, 50, 100, 200, 400 and 600 μL L -1 . The time of sedation ranged from 7 to 31 seconds and the recommended concentration was 10 or 25 μL L -1 for both essential oils. The best times for anaesthesia and recovery were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In addition, another study showed the use of C. exuosus essential oil for the anesthesia in Oreochromis niloticus. Notely, the main active ingredients in the C. exuosus essential oil are geranial and neral (Netto et al, 2017). Cinnamaldehyde, a Trpa1 agonist, acts as a local anesthetic by inhibiting voltage-gated sodium channels in sensory neurons (Boonen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, another study showed the use of C. exuosus essential oil for the anesthesia in Oreochromis niloticus. Notely, the main active ingredients in the C. exuosus essential oil are geranial and neral (Netto et al, 2017). Cinnamaldehyde, a Trpa1 agonist, acts as a local anesthetic by inhibiting voltage-gated sodium channels in sensory neurons (Boonen et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…72 The EOs of basil (Ocimum basilicum) and lemongrass (Cymbopogum flexuosus) were tested as anaesthetics for Nile tilapia; both are recommended for sedation at a concentration of 10-25 ml/l, and for anaesthesia at a concentration of 400 ml/l for basil EO and 600 ml/l for lemongrass EO. 75 In juvenile tambaqui (Colossoma macropomum), the EO of citronella (Cymbopogon nardus) at a concentration of 200 ml/l was sufficient to induce sedation, while the concentration range of 400-600 ml/l was adequate to induce deep anaesthesia. A concentration of 600 ml/l was sufficient to promote a rapid induction in less than 3 min and a recovery from deep anaesthesia in less than 5 min.…”
Section: Essential Oilsmentioning
confidence: 99%
“…The EOs of basil ( Ocimum basilicum ) and lemongrass ( Cymbopogum flexuosus ) were tested as anaesthetics for Nile tilapia; both are recommended for sedation at a concentration of 10–25 µl/l, and for anaesthesia at a concentration of 400 µl/l for basil EO and 600 µl/l for lemongrass EO. 75…”
Section: Anaesthetic Agents Used For Research In Adult Fishmentioning
confidence: 99%
“…However, the edible safety of fish treated with anesthetics has aroused great concern, and questions remain about the efficiency and safety of these synthetic anesthetics as residues in human food, leading researchers to seek easily available, low-cost, and safe anesthetics [ 18 , 19 ]. Plant extracts or essential oils may be viable alternatives to fish anesthetics, such as basil Ocimum basilicum essential oil, rubber seeds ( Hevea brasiliensis ), and tuba root ( Derris elliptica ) [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%